Gully controlling practices associated with soil geotechnical properties in the subhumid Ethiopian highlands - Meseret Belachew Addisie; Hailu Menale Wassie (Brawijaya University, 2021)
Check dams are business as usual practices used to avert gully erosion development and sedimentation in the downstream areas of the humid highlands of Ethiopia. We investigated the status of check dams and their relationship with geotechnical soil properties in the sub-humid Fogera floodplain. The density of gullies in the area was more sever having about 3.6 km km-2 which shows the severity of gully erosion. Thirty-two dams constructed and monitored over one rainy season. In the beginning of the rainy season, all the dams filled up with sediments, and at the end of the monitoring period ninety five percent of them had destroyed and the remainings had partially destroyed and had sediments accumulated on one side of the gully bank. The longitudinal gradient of streams above the dams decreased due to sedimentation. The morphological change of the gully showed an increase in width-depth ratio, gully bank erosion, and sediment aggradation in the gully bed. We found that the amount of sediments deposited behind the dams were higher than the amount of eroded material. The higher clay content and Atterberg limits increased soil erodibility once the gully channel formed. The erodibility and saturation in these soils were highly contributing to gully development and reducing the effectiveness of check dams. In conclusion, it is better to adopt an integrated novel practice to control gullying than solely using check dams.